Analisis Hukum Investasi di Pelabuhan Berdasarkan Undang- Undang No 17 Tahun 2008 Tentang Pelayaran sebagai Upaya Pembangunan Ekonomi Nasional - Recca Ayu Hapsari (KEADILAN PROGRESIF, 2015)
Fundamental changes that have a direct impact on the national economy , is globalization and trade liberalization . Globalization and trade liberalization means that the world market will be more open to our products , and vice versa domestic potential we will  be more open as well for the influx of capital, technology and ideas that can bring progress . Judging from the demand side , consumer goods and services will require an increasingly diverse and demanding higher quality assurance . Higher consumer demands it should encourage economic operators in the sector of manufacturing and service industries to translate consumer tastes at the opportunity to invest in particular on a cruise.